(untitled) (Journal of the Management Sciences, 2024)
Celebrity endorsement in recent times has become a veritable tool in achieving sustainable sales of products and services by business managers. It is based on this, that this study examined celebrity endorsement and consumer choice of product in Anambra State, Nigeria as the objective of the study. The study was narrowed down to Onitsha local government Area of the State. This is because of presence of various consumer markets the city is hosting. The study adopted a survey research design with a population of 250 consumers selected randomly, and 207 copies of questionnaire were retrieved and used for the study. A Likert structured questionnaire format was deployed for data collection, which was tested for validity using face and content method while its reliability was assessed using Cronbach Alpha reliability test for internal consistency where an alpha level of .999 was obtained signaling a good consistency level. The data generated was analyzed using Mean, and Hypothesis was tested using simple regression on Statistical packages for Social Science at 5% level of significance. The findings reveal that, there is a positive effect of celebrity influence on customer conviction on patronage r= 0.728, n=207-1=206 and p=0.25. Thus, since p value is less than 0.05, hence, there is positive effect of celebrity influence on customer conviction on patronage of a product. Therefore, the study recommended that, product or service management should adopt criteria for adopting celebrity endorsement if they want to influence consumer choice of products.